Azerbaijan - Building Competitiveness : An Integrated Non-Oil Trade and Investment Strategy, Volume 2. Background Papers - World Bank (Washington, DC, 2013)
Azerbaijan's early transition to an independent, market-based economy has been tumultuous, entailing significant economic costs, and social impacts. Yet, unlike many transition economies, sound economic reforms since 1995, have enabled the country to achieve macroeconomic stability, and resume growth. Notwithstanding, the impact on poverty reduction has been modest, particularly in the case of the urban poor who did not benefit from land reform. To this end, the Government is committed to a poverty reduction program, through macroeconomic and structural reforms, to alleviate poverty and improve living conditions. This report looks at the role of trade and investment in reducing poverty, taking into account the fact that the oil sector, expected to be the primary driver of growth, accounts for 75 percent of the total increase in real output. Although projected growth in the non-oil sectors is 6.3 percent, and while relatively slow compared to the expected rapid growth in the oil sector, it would be a significant improvement over the average 3.8 percent growth rate achieved between 1995 and 2001. This base case growth scenario would reduce the incidence of poverty from 50 percent, to 30 percent, and would reduce the share of those in extreme poverty from 17 percent, to 7 percent by 2010. The report stipulates the exchange rate does not appear to hamper competitiveness, but remains a future challenge. Given the fact that private sector is liquidity constrained (the capital market is underdeveloped), fiscal policy will provide main policies to manage the oil windfall successfully, as well as accumulating the excess oil revenues in the Oil fund abroad, providing a fiscal sterilization, thus avoiding excessive real exchange rate appreciation. This study is a diagnostic of the non-oil trade and investment environment in Azerbaijan. Its primary objective is to define a strategy for enhancing competitiveness at the macro- and micro-levels, and increase trade and inward investment in the non-oil sector to assist in poverty reduction efforts. The strategy implements one of the key objectives of the Government's program, i.e., enabling income generating opportunities, and jobs in the non-oil sector. The analytical approach includes such program; and various strategies and analyses of the Government, donors, international financial institutions, private sector groups, and NGOs; relevant analyses of the Bank and International Monetary Fund (IMF); as well as three assessments conducted for this report: an analysis of administrative barriers to inward investment; an evaluation of trade policy and market access agreements of Azerbaijan, including issues related to the World Trade Organization (WTO) accession; and, a pilot study of the potential for a fruit and vegetable processing cluster.